Extração, caracterização e avaliação bioativa do extrato de Rumex acetosa - Santos, ênio Rafael de Medeiros (2013)
Studies show the great influence of free radicals and other oxidants as responsible for aging and degenerative diseases. On the other hand, the natural phenolic compounds has shown great as antioxidants to inhibit lipid peroxidation and lipoxygenase in vitro. Among these, is highlighted trans-resveratrol ( 3,5,4 `- trihydroxystilbene ) phenolic compound , characterized as a polyphenol stilbene class. The vegetables popularly known as "Azedinha" (Rumex Acetosa) has trans-resveratrol in its composition and from this, the present work aimed to study on the supercritical extraction and conventional extraction (Soxhlet and sequential) in roots of Rumex Acetosa, evaluating the efficiency of extractive processes, antioxidant activity, total phenolic content and quantification of trans-resveratrol contained in the extracts. Extractions using supercritical CO2 as solvent, addition of co-solvent (ethanol) and were conducted by the dynamic method in a fixed bed extractor. The trial met a 23 factorial design with three replications at the central point, with the variable reply process yield and concentration of trans-resveratrol and pressure as independent variables, temperature and concentration of co-solvent (% v/v). Yields ( mass of dry extract / mass of raw material used ) obtained from the supercritical extraction ranged from 0,8 to 7,63 % , and the best result was obtained at 250 bar and 90 °C using the co-solvent 15% ethanol (% v/v). The value was calculated for YCER a flow rate of 1,0 ± 0,17 g/min resulting in 0,0469 CO2 ( g solute / g solvent ). The results of the mass yield varied between conventional extractions 0,78 % ( hexane) and 9,97 % (ethanol). The statistical model generated from the data of the concentration of trans-resveratrol performed as meaningful and predictive for a 95% confidence. GC analysis on HPLC (High Performance Liquid Chromatography), transresveratrol was quantified in all extracts and concentration values ranged between 0,0033 and 0,42 ( mg / g extract) for supercritical extracts and between 0,449 and 17,046 (mg / g extract) to conventional extractions and therefore, the Soxhlet extraction with ethanol for more selective trans-resveratrol than the supercritical fluid. Evaluation of antioxidant (radical method to sequester 2,2- diphenyl-1- picryl - hydrazyl - DPPH) the supercritical extracts resulted in EC50 values (concentration effective to neutralize 50% of free radicals) of between 7,89 and 18,43 mg/mL , while resulting in a Soxhlet extraction with EC50 values in the range of 6,05 and 7,39 mg/mL. As for quantification of the phenolic compounds (Method Spectrophotometer Folin-Ciocalteau) the supercritical extracts resulted in values between 85,3 and 194,79 mg GAE / g extract, whereas values derived from the Soxhlet extract resulted in values between 178,5 and 237,8 mg GAE / g extract. The high antioxidant activity can not be attributed solely to the presence of phenolic compounds, but the presence of other antioxidants in the existing Rumex acetosa